EFFECT OF CROP COVER AND STAGE OF CROP GROWTH ON SOIL L-ASPARAGINASE , ALKALINE AND ACID PHOSPHATASE IN AN ALFISOL - and M.MADHAVI, J. ARUNAKUMARI, P. CHANDRASEKHAR RAO, G. PADMAJA, R. SUBHASH REDDY (The Journal of Research, PJTSAU, 2017)
A pot culture experiment was conducted in an Alfisol in the greenhouse of Department of Soil Science and Agricultural Chemistry, Rajendranagar, Hyderabad, to study the influence of crop cover and stage of crop growth on soil enzymes L-asparaginase, acid and alkaline phosphatases activities. The experiment was undertaken with three cereals – rice, sorghum and maize, two oil seeds – groundnut and sesame, two pulses – green gram and black gram, two vegetables – bhendi and brinjal. The experiment was conducted using crops as treatments in Completely Randomized Block design with three replications along with the uncropped control. The results obtained with regard to the effect of these crops soil L-asparaginase activity showed that there was an increase in enzyme activity with age of the crop and it varied with plant species grown. The enzyme activity increased from 0 days and reached peak level at 60 days for L-asparaginase and 45 days for acid and alkaline phosphatases. The increase in L-asparaginase activity (expressed as µg of NH4+ released g -1 soil h-1) ranged from 3.59 to 10.61 in groundnut (Archis hypogaea), from 3.56 to 6.24 in black gram (Vigna mungo), from 3.54 to 6.14 in - green gram (Vigna rabiata), from 3.47 to 5.95 in sesame (Sesamum indicum), from 3.49 to 5.45 in rice (Oryza sativa L.), 3.46 to 5.14 in maize (Zea mays), from 3.35 to 5.08 in sorghum (Sorghum vulgare), from 3.29 to 4.75 in brinjal (Solanum melongena) and from 3.32 to 4.87 in bhendi (Abelmoschus esculentus). The activity of L-asparaginase, acid and alkaline phosphatase under different crop coverages followed the decreasing order groundnut > blackgram > greengram > sesame > rice > maize > sorghum > brinjal > bhendi. The presence and type of plants grown on a soil have shown a marked influence on enzyme activities, more over the levels of enzymes activity declined to nearly the original levels at harvest.